2021
DOI: 10.1038/s41467-021-23702-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of GTPase-mediated mitochondrial ribosome biogenesis and recycling

Abstract: Ribosome biogenesis requires auxiliary factors to promote folding and assembly of ribosomal proteins and RNA. Particularly, maturation of the peptidyl transferase center (PTC) is mediated by conserved GTPases, but the molecular basis is poorly understood. Here, we define the mechanism of GTPase-driven maturation of the human mitochondrial large ribosomal subunit (mtLSU) using endogenous complex purification, in vitro reconstitution and cryo-EM. Structures of transient native mtLSU assembly intermediates that a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 51 publications
2
45
1
Order By: Relevance
“…This is also the case for all the maturation factors involved in mitoribosome biogenesis. Recently, several studies managed to capture mitoribosome assembly intermediates from humans [ 127 , 128 , 129 , 130 , 131 ] and kinetoplastids [ 95 , 98 , 99 , 132 , 133 ], describing different steps and factors involved in the maturation of the large and small mitoribosomal subunits. A portion of these factors were previously described by non-structural means [ 59 , 134 , 135 , 136 ], but most of them were described for the first time with these studies, and most importantly, directly observed in action.…”
Section: Functions and Modes Of Action Of Mitoribosome-specific Proteinsmentioning
confidence: 99%
“…This is also the case for all the maturation factors involved in mitoribosome biogenesis. Recently, several studies managed to capture mitoribosome assembly intermediates from humans [ 127 , 128 , 129 , 130 , 131 ] and kinetoplastids [ 95 , 98 , 99 , 132 , 133 ], describing different steps and factors involved in the maturation of the large and small mitoribosomal subunits. A portion of these factors were previously described by non-structural means [ 59 , 134 , 135 , 136 ], but most of them were described for the first time with these studies, and most importantly, directly observed in action.…”
Section: Functions and Modes Of Action Of Mitoribosome-specific Proteinsmentioning
confidence: 99%
“…Recently, the GTP-binding protein GTPBP6, a human homolog of bacterial HflX, was identified as an essential mitochondrial protein with dual functions [ 132 ]. In addition to its role in mitoribosome biogenesis, GTPBP6 acts as an alternative recycling factor in human mitochondria [ 132 , 133 ]. Similar to the canonical and HflX-driven recycling systems in bacteria, GTPBP6 binding to the 55S mitoribosome facilitates disruption of the critical B2a intersubunit bridge by helix 69 dislocation.…”
Section: Ribosome Rescue In Human Mitochondriamentioning
confidence: 99%
“…However, GTPBP6 utilizes a different mechanism to dissociate mitoribosomes. Cryo-EM analysis of post-splitting mtLSU complexes revealed that GTPBP6 abstracts helix 69 by insertion of the Trp107 residue [ 133 ]. Interestingly, kinetic measurements suggest that GTPBP6-mediated ribosome splitting occurs more efficiently on vacant ribosomes or on PoTC [ 132 ].…”
Section: Ribosome Rescue In Human Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, first mechanistic insights into the assembly of mitoribosomes were obtained by structure determinations of the kinetoplastid small (mt-SSU) ( 31 , 32 ) and large subunit (mt-LSU) ( 32 34 ) as well as late-stage human mt-LSU assembly intermediates ( 35 40 ). The study of untagged Trypanosoma brucei mt-SSU resulted in several cryogenic electron microscopy (cryo-EM) structures of assembly intermediates that illustrated possible assembly progression.…”
mentioning
confidence: 99%